An optimised scattering power decomposition method oriented to ship detection in polarimetric synthetic aperture radar imagery - Lu Fang; Wenxing Mu; Ning Wang; Tao Liu (IET Radar, Sonar & Navigation)
Abstract This paper describes an optimised scattering power decomposition method suitable for ship detection in polarimetric synthetic aperture radar imagery. Based on the principal component analysis technique for dimension reduction and the scattering power decompositions with strong physical interpretation, a novel optimised scattering power decomposition model is proposed which comprises surface scattering, double‐bounce scattering, ±45° oriented dipole, and volume scattering components. Wherein, the oriented dipole component can be used to characterise the compounded scattering of the target which is composed of even‐bounce and odd‐bounce reflectors. Furthermore, pocket algorithm and support vector machine are adopted to solve linear non‐separable problems under complex experimental conditions in this study. Extensive experiments carried out on RADARSAT‐2 data and NASA/JPL AIRSAR data show that the oriented dipole component significantly contributes to the optimised four‐component decomposition method and can play a vital role in ship detection. Compared to other scattering power decompositions, the optimised decomposition method not only achieves better performance but is more in accordance with the real scattering mechanisms, which is more applicable to ship detection.